Pengaruh Dosis Pupuk Organik Cair Daun Lamtoro terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa l.) Varietas Nauli-F1 - Odang Hidayat; Aep Suharyana (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2019)
The research was conducted in Padasari Village, Cimalaka Sub-district, Sumedang District, from June to September 2018, located at an altitude of 600 m asl. The objective of experiment was to study the effect of dosage of lamtoro leaf organic fertilizer to growth and yield of Pakcoy (Brassica rapa L.) plant varieties Nauli-F1. The research was conducted by experimental approach through field experiment. The design used in the experiment was a simple randomized block design consisting of six treatments and four replications. The dose of liquid organic fertilizer treatment Lamtaro leaves consist of: A : 0 L Ha-1, B: 100 L Ha-1, C: 200 L Ha-1, D: 300 L Ha-1, E: 400 L Ha-1, and F: 500 L Ha-1. The result of experiment showed that the use of lamtoro liquid organic fertilizer gave a good effect on all observation variables. The dose of Lamtoro leaf organic fertilizer 500 L Ha-1 showed the best result an plant height, number of leaves, net weight per plant, net weight per plot, and the shoot root ratio.